Evaluasi Kualitas Website Pemerintah Desa Sidoluhur Godean Berdasarkan Persepsi Pengguna - Fajar Nugroho; Bambang Soedijono; Armadyah Amborowati (Sekolah Tinggi Maritim Yogyakarta, 2019)
The aim of this study is to determine the relationship between the ideal level of expectations and the user's actual perceptions of the web quality services provided by the The Sidoluhur Godean Village, as well as providing solutions and managerial implications that can be planned to improve the quality of the website services. The method used to perform the evaluation through the integration of calculation webqual variables modifications approach within the framework of Structural Equation Modelling (SEM) and Importance Performance Analysis (IPA). This research, shows there is a positive and significant relationship among the variables of website service quality, satisfaction levels, and the intensity of system use. This relation forms the research conceptual model. The attributes that are necessary to get attention is the problem of updating information content, detailed information, user interaction security, image appropriation, font's suitability and speed time access to view website.